Analysis of LazLive Utilization in Mobile Applications Lazada at Sahoor Time - Guslim, Angga; Kusnadi, Karen; Irwansyah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Live streaming is becoming a global trend that is popularly used in many sectors, including e-commerce. Lazada, as one of the largest app-based e-commerce in Southeast Asia, also utilizes the use of live streaming by initiating LazLive (Lazada Live Streaming) as one of the featured features in their mobile application. Unlike most e-commerce such as Tokopedia and Shopee, Lazada as a brand also creates official live stream content from the company through a series of special programs, which are actual features as well as customized marketing messages. This study aims to examine Lazada's strategy of creating a new live streaming method in its mobile application (LazLive). Based on the view of the social construction theory of technology, this study analyzed 23 Lazada live streams held from March 23 to April 24, 2023, during sahoor time. Using a descriptive qualitative approach, this study used content analysis techniques. The results found that (1) Lazada personalized several of its live streaming features to match the feel of the program, and (2) Lazada continues to update its features according to customer needs and feedback. (3) LazLive received a positive response from Lazada app users and contributed to the number of reviews received by the Lazada mobile app in the Google Play Store. All the innovations that Lazada provides through LazLive are expected to increase application consumers and the welfare of sellers.